(untitled) (Fiep Bulletin - online, 2014)
The phytotherapy is therapeutic resource which is characterized by the use of medicinal plants in its various pharmaceutical forms. Its use is based on the consolidation of practices and alternative treatments, and is maintained over time through the accumulation of information that has been passed through the generations. It is a descriptive study conducted with 80 users of Living Pharmacy Unit of the municipality of Governador Dix-Sept. Rosado (RN), Northeast / Brazil. It used a structured questionnaire to data-collection between August and September, 2007, after approval by the Ethics in Research Committee. The data were analyzed on Epi-Info 3.4 Windows. The predominant socio-demographic aspects of the users were the predominant female (60.0%), aged from 18 to 39 years (60.0%), with high school (33.8%), farmers (43.8%) and family monthly income of 1 to 2 minimum wages (55.0%). The most frequent morbidities were the respiratory tract (30.0%), neurological (22.5%), hypertension (18.8%) and osteomuscular (15.0%) diseases. Users had little (61.3%) and none (27.5%) knowledge about phytotherapy. Most of the prescriptions were performed by doctors (97.0%), being the most used phytotherapeutic, Cumaru syrup (67.5%), Erva Cidreira capsule (30.0%) and Aroeira cream (13.7%). We think that the expansion of phytotherapy use by the population is of prime importance. Therefore, it is clear the need for intervention strategies in health education to improve the knowledge level and the proper use of these products.